Association between intake of dairy products and short-term memory with and without adjustment for genetic and family environmental factors: A twin study. Issue 2 (April 2016) - Ogata, Soshiro; Tanaka, Haruka; Omura, Kayoko; Honda, Chika; Hayakawa, Kazuo; ,
Summary: Background & aims: Previous studies have indicated associations between intake of dairy products and better cognitive function and reduced risk of dementia. However, these studies did not adjust for genetic and family environmental factors that may influence food intake, cognitive function, and metabolism of dairy product nutrients. In the present study, we investigated the association between intake of dairy products and short-term memory with and without adjustment for almost all genetic and family environmental factors using a genetically informative sample of twin pairs. Methods: A cross-sectional study was conducted among twin pairs aged between 20 and 74. Short-term memory was assessed as primary outcome variable, intake of dairy products was analyzed as the predictive variable, and sex, age, education level, marital status, current smoking status, body mass index, dietary alcohol intake, and medical history of hypertension or diabetes were included as possible covariates. Generalized estimating equations (GEE) were performed by treating twins as individuals and regression analyses were used to identify within-pair differences of a twin pair to adjust for genetic and family environmental factors. Data are reported as standardized coefficients and 95% confidence intervals (CI). Results: Analyses were performed on data from 78 men and 278 women. Among men, high intake of dairy products was significantly associated with better short-term memory after adjustment for the possible covariates (standardized coefficients = 0.22; 95% CI, 0.06–0.38) and almost all genetic and family environmental factors (standardized coefficients = 0.38; 95% CI, 0.07–0.69). Among women, no significant associations were found between intake of dairy products and short-term memory. Subsequent sensitivity analyses were adjusted for small samples and showed similar results. Conclusions: Intake of dairy product may prevent cognitive declines regardless of genetic and family environmental factors in men.